Partnering With a Pest: Genomes of Hemlock Woolly Adelgid Symbionts Reveal Atypical Nutritional Provisioning Patterns in Dual-Obligate Bacteria. (1st June 2018) - Weglarz, Kathryn M; Havill, Nathan P; Burke, Gaelen R; von Dohlen, Carol D
Abstract: Nutritional bacterial symbionts enhance the diets of sap-feeding insects with amino acids and vitamins missing from their diets. In many lineages, an ancestral senior symbiont is joined by a younger junior symbiont. To date, an emergent pattern is that senior symbionts supply a majority of amino acids, and junior symbionts supply a minority. Similar to other hemipterans, adelgids harbor obligate symbionts, but have higher diversity of bacterial associates, suggesting a history of symbiont turnover. The metabolic roles of dual symbionts in adelgids and their contributions to the consortium are largely unexplored. Here, we investigate the symbionts of Adelges tsugae, the hemlock woolly adelgid (HWA), an invasive species introduced from Japan to the eastern United States, where it kills hemlock trees. The response of hemlocks to HWA feeding has aspects of a defensive reaction against pathogens, and some have speculated that symbionts may be involved. We sequenced the genomes of " Ca. Annandia adelgestsuga" and " Ca . Pseudomonas adelgestsugas" symbionts to detail their metabolic capabilities, infer ages of relationship, and search for effectors of plant defenses. We also tested the relationship of " Ca . Annandia" to symbionts of other insects. We find that both symbionts provide nutrients, but in more balanced proportions than dual symbionts of other hemipterans. The lesser contributions of the senior " Ca . Annandia" support our hypothesis for symbiont replacements in adelgids. Phylogenomic results were ambiguous regarding the position of " Ca . Annandia". We found no obvious effectors of plant defenses related to insect virulence, but hypothetical proteins in symbionts are unknown players.